An investigation into rural and urban pupils' alternative conceptions of the concept "animal" - Tema, Botlhale Octavia (School of Education, 2023)
This is a comparative study of the conceptions that rural and urban black pupils hold with regard to the concept "animal". The study recognises the fact that the concept animal is important to the study of biology and that effective learning of the subject may be hampered if pupils hold different conceptions from those accepted in the subject. It was envisaged that the pupils would as a result of the different cultural milieu from which they come, hold different conceptions. This notion is based on the idea that one's conceptions are derived from one's conceptual ecology. It was also expected that pupils would have idiosyncratic conceptions based on their individual attempts to explain reality and that this would be a reflection of their cognitive development. The method of interview - about - instances developed by 0sborne(l979), was used in the study. This method is based on Piaget's method of clinical interviews. The subjects - 30 rural and 30 urban pupils, were presented with 19 cards depicting some familiar instances and no instances of the concept "animal". They were then asked to classify each picture and state the reasons for their classification. They were later asked to choose four reasons from a list of 26 which they consider best for classifying an animal. - V - A science reasoning task designed by S